2020
DOI: 10.3390/magnetochemistry6030039
|View full text |Cite
|
Sign up to set email alerts
|

Designing Magnetic NanoMOFs for Biomedicine: Current Trends and Applications

Abstract: Metal–organic frameworks (MOFs) have shown a great potential in biomedicine due to their promising applications in different fields, including drug delivery, thermometry, theranostics etc. In this context, the development of magnetic sub-micrometric or nanometric MOFs through miniaturization approaches of magnetic MOFs up to the nanoscale still represents a crucial step to fabricate biomedical probes, especially in the field of theranostic nanomedicine. Miniaturization processes have to be properly designed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…Zr is an essential microelement for the human body, with an oral lethal dose (LD 50 ) of 4.1 g kg –1 . The LD 50 value for BTC as a biofriendly and exogenous organic linker used to prepare MOF-808 is 8.4 g kg –1 . , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zr is an essential microelement for the human body, with an oral lethal dose (LD 50 ) of 4.1 g kg –1 . The LD 50 value for BTC as a biofriendly and exogenous organic linker used to prepare MOF-808 is 8.4 g kg –1 . , …”
Section: Introductionmentioning
confidence: 99%
“…The LD 50 value for BTC as a biofriendly and exogenous organic linker used to prepare MOF-808 is 8.4 g kg −1 . 95,96 The surface chemistry of a given drug-delivery system identifies its interaction with the media, enhancing stability and dispersion and providing the potential for the drug to overcome physiological boundaries while serving as target delivery systems. In this regard, surface modification offers great potential for the development of high-efficiency MOFbased drug-delivery systems; however, the multiple synthetic steps involved in their synthesis, surface modification, and drug loading can impede their efficient manufacture.…”
Section: Introductionmentioning
confidence: 99%
“…6–8 CPs are infinite coordination frameworks built by the self-assembly of metal ions and organic linkers to form various architectures in different dimensions. 9–13 MOFs are a subclass of CPs, possessing potential voids that can lead to permanent porosity as a unique feature, which are an important class of materials due to their potential practical applications in various fields such as sensing, 14 adsorption, 15 wastewater treatment, 16 photocatalysis, 17 biomedicine, 18 etc. 19,20…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Because of their intrinsic porosity they have attracted ever-growing interest in several applications ranging from gas storage and separation, catalysis, chemical sensing, to biomedicine. [12][13][14][15] Noteworthy Long. et al recently reported on the unprecedented adsorption behaviour shown by diamine-appended MOFs, which maintain affinity for CO2 under moisture exposure and show excellent long-term stability, both crucial requirements for CO2 capture.…”
Section: Introductionmentioning
confidence: 99%